Peran Wali Nikah dalam Perkawinan Persinggungan Pancasila dengan Hukum Islam dan Konstitusi: The Role of Marriage Guardians in Marriages: The Intersection of Pancasila with Islamic Law and the Constitution - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Mahira Arrosyida; Malika Ayudia Cahyani; Erika Febriyanti (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
The role of marriage guardians is discussed in the context of Islamic law, Pancasila and the Indonesian constitution, as well as challenges and solutions in their implementation. The marriage guardian has a central function in Islamic law as the party responsible for witnessing and ratifying the marriage contract. This research explores how the role of marriage guardian is integrated with Pancasila values ​​which emphasize justice and equality, and how this is in line with provisions. The research method used in this research is a qualitative descriptive research method, taking the research location at the Polokarto District Religious Affairs Office. The population and sampling method used was purposive sampling while the respondents were heads and employees at the KUA office and husband and wife couples. The types and sources of data used are primary and secondary data. The data collection technique uses interviews and literature study, while the data analysis technique is interactive analysis. The results of the research show that according to Islamic law the role of the guardian in marriage is very important because all marriages carried out must be with the permission and blessing of the marriage guardian, especially the guardian of the lineage, namely the father, because the marriage is based on the teachings of the Islamic religion. Marriage without the guardian's permission is invalid. This is emphasized in Article 19 KHI. Having a marriage guardian in marriage can play a role in protecting women from possible harm in their marriage household, and by first fulfilling the conditions and pillars of marriage and what is no less important is having permission and blessing from the marriage guardian, especially the father before the marriage. carried out will have an influence on psychological aspects for the continuity and peace of the married household of the daughter.